2022
DOI: 10.3390/ma15207344
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Strength and Impact of Raw Ingredients of Cement Mortar Incorporating Waste Glass Powder Using Machine Learning and SHapley Additive ExPlanations (SHAP) Methods

Abstract: This research employed machine learning (ML) and SHapley Additive ExPlanations (SHAP) methods to assess the strength and impact of raw ingredients of cement mortar (CM) incorporated with waste glass powder (WGP). The data required for this study were generated using an experimental approach. Two ML methods were employed, i.e., gradient boosting and random forest, for compressive strength (CS) and flexural strength (FS) estimation. The performance of ML approaches was evaluated by comparing the coefficient of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 66 publications
0
14
0
Order By: Relevance
“…As the error distribution shows, the random forest model is more precise than bagging regressors. In the random forest training procedure, each tree generates regression, and the forest with the most votes is chosen as the model, resulting in increased model accuracy [ 50 ]. However, the results of the bagging regressor model were also found to be accurate.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As the error distribution shows, the random forest model is more precise than bagging regressors. In the random forest training procedure, each tree generates regression, and the forest with the most votes is chosen as the model, resulting in increased model accuracy [ 50 ]. However, the results of the bagging regressor model were also found to be accurate.…”
Section: Results and Analysismentioning
confidence: 99%
“…There has been a rise in the use of ML methods for forecasting building materials performance [ 46 48 ]. Only a few articles have dealt with predicting the features of cement-based materials modified with RGP [ 32 , 49 , 50 ], while most earlier ML research has focused on the strength of traditional cement-based materials [ 51 53 ]. However, no study was found in the literature for the prediction of CS of cement-based materials containing RGP after the acid attack using ML methods.…”
Section: Introductionmentioning
confidence: 99%
“…The SHAP [ 54 , 55 ] framework explains the output of machine learning models by employing principles from game theory. This method quantifies the contributions of features to the predictions made by the model.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of each attribute on the SHAP value is roughly averaged across all possible permutations. Furthermore, the absolute SHAP value represents the degree of the feature's impact on model prediction, making it possible to utilize it as a measurement of feature relevance [46].…”
Section: Shapley Additive Explanation (Shap)mentioning
confidence: 99%